9,9‐Dilithiofluorene: the first crystal‐structure analysis of an α,α‐Dilithiated hydrocarbon - Linti, Gerald W.; Rodig, Alexander; Pritzkow, Hans (Angewandte Chemie. International edition, 2002)
Six‐coordinate carbon: 9,9‐Dilithiofluorene-thf complex (see picture) crystallizes as chains of lithium atoms which are alternately bridged by fluorenylidene and THF units. These polymer chains are held...